Organic and Inorganic Fertilizer Effects on the Growth and Yield of Maize in a Dry Agro-Ecology in Northern Ghana. Issue 1 (2nd January 2016) - Kanton, R. A. L.; Prasad, P. V. V.; Mohammed, A. M.; Bidzakin, J. K.; Ansoba, E. Y; Asungre, P. A.; Lamini, S.; Mahama, G.; Kusi, F.; Sugri, I.
Abstract: Declining maize ( Zea mays L.) yields caused by factors, such as inherently poor soils, continuous cropping of cereal after cereal, high cost and unavailability of chemical fertilizers, continuous crop-residue removal, and soil erosion and run-off, have all contributed to low soil fertility and reduced maize yields in northern Ghana. To address this negative trend, a three-year field trial was conducted at the Manga Agricultural Research Station in the Upper East Region of Ghana, which represents a Sudan Savannah agro-ecology. The treatments comprised 11 available sources of organic and inorganic fertilizers, which are soil fertility management practices used by peasant farmers. A randomized complete block design with four replications was used. The results revealed that the inorganic fertilizers with micro-nutrients, such as S, Zn, and Mg, (i.e., Actyva and 21:10:10:2 S) produced taller plants, caused earlier tasseling and silking, and produced higher grain yields on account of increased straw yields, plant height, stem girth, grain size, and harvest indices than organic fertilizers. Poultry manure and sheep manure were the best among the organic sources evaluated. Whereas most of the fertility management options accrued net benefits of more than 150.00, the goat droppings and town waste had low net benefits of 44.30 and 17.00, respectively, indicating low gains on investment and therefore, not profitable for field application.